Non-tuberculous mycobacteria infection treated with intermittently inhaled high-dose nitric oxide. Issue 10 (28th October 2021) - Goldbart, Aviv; Gatt, Dvir; Golan Tripto, Inbal
Abstract : Mycobacterium abscessus is an emerging multidrug-resistant non-tuberculous mycobacterium (NTM) with high prevalence in patients with cystic fibrosis. However, studies on antimicrobial susceptibilities and effective treatments against M. abscessus are still limited. Nitric oxide (NO) is important in innate immune response to various infections, including mycobacterial infections. In this case study, we describe a compassionate treatment of inhaled NO (iNO) at 150–250 ppm for 4 weeks. The dosing strategy proposed for this treatment was selected to minimise the potential of adverse events, while maximising the antibacterial effectiveness of NO, and was found to be safe, well tolerated and resulted in positive clinical findings including improvement in patient well-being, CT scan values, quality of life and bacterial load. Taken together, these observations may indicate that iNO could play a crucial role and potentially serve as a reliable option in the treatment of patients with chronic refractory NTM lung infection.